PERCEPTIONS OF PHYSICS EDUCATION STUDENTS AT UNIVERSITAS NEGERI MEDAN ON THE ROLE OF PHYSICS EDUCATION IN SUSTAINABLE DEVELOPMENT GOALS - Simanjuntak, Yanthy Leonita Perdana; Rangkuti, Muhammad Aswin; Hardianti, Tuti (JURNAL EDUSCIENCE, 2025)
Purpose – This study explores the perspectives of physics education students to understand the integration of SDGs in physics learning. Furthermore, to examine these perspectives, it is important to determine the extent of physics education students’ perceptions of SDGs.Methodology – This research adopts a quantitative questionnaire and is also supported by qualitative approaches. There are 120 physics education students from Universitas Negeri Medan selected through purposive sampling. The questionnaire consists of Likert-scale items, followed by semi-structured interviews with 10 randomly selected respondents. Triangulation was applied to integrate both datasets, providing a comprehensive understanding of students’ knowledge, attitudes, and experiences related to ESD in physics learning.Findings – The results reveal that students perceive physics as a key discipline that contributes to addressing global challenges, including climate change, renewable energy innovation, and sustainable technology development. Physics is viewed as providing conceptual and analytical frameworks essential for sustainability oriented problem solving. However, students’ literacy regarding the SDGs remains limited. Many participants demonstrate general awareness but lack the ability to explicitly connect SDG concepts with physics topics or classroom practices. The integration of ESD in physics learning is still partial.Contribution – One of the contributions of this study presents a significant opportunity to begin integrating physics education, particularly in relation to the perceptions of physics education students, with the SDGs. This study also make a valuable reference for understanding the real contribution of physics education toward achieving the SDGs.